Off-Label Use of Venetoclax in Patients With Acute Myeloid Leukemia: Single Center Experience and Data From Pharmacovigilance Database - Gozzo, Lucia; Vetro, Calogero; Brancati, Serena; Longo, Laura; Vitale, Daniela Cristina; Romano, Giovanni Luca; Mauro, Elisa; Fiumara, Paolo Fabio; Maugeri, Cinzia; Parisi, Marina Silvia; Dulcamare, Ilaria; Garibaldi, Bruno; et al. (Frontiers in Pharmacology, 2021)
The potent oral inhibitor of BCL2, venetoclax (VEN), used to treat adults with chronic lymphocytic leukaemia, has been approved in US for the treatment of naïve patients with acute myeloid leukemia (AML) unfit for intensive chemotherapy and recently in Europe, too. However, the drug has been used for years in combination with hypomethylating agents (HMAs) in patients not eligible to other treatment option, according to the so-called off-label use. We collected real-world data about patients treated with VEN+HMAs in the context of a pharmacovigilance project focused on the evaluation of the safety and effectiveness of drugs used for unapproved indication in Italian hospitals. From March to December 2020, 24 patients started treatment with VEN combined with HMAs. 21 patients have been assessed for response. Eleven (52%) patients reached complete remission (CR), and 3 patients (14%) CR with partial hematological recovery (CRh), with a median duration of response of 4.5 months (range 0.5-12.5). Nineteen patients experienced at least 1 adverse drug reaction (ADR), mostly serious, including 3 deaths (9% of ADRs; 12.5% of patients) in febrile neutropenia. Hematological toxicities and infections (cytopenia, neutropenia, febrile neutropenia, sepsis), were the most reported ADRs (84.4%). In general, neutropenic fever occurred more frequently in patients treated with decitabine (7 out of 9, 78%) compared to azacitidine (5 out of 15, 33%; p=0.03), whereas response assessment did not differ based on used HMA (p=0.1). These results confirm the risk-benefit profile of VEN in a real-world setting of patients with no adequate therapeutic options.